2013
DOI: 10.2147/dddt.s43035
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of 6-mercaptopurine-coated magnetite nanoparticles as a drug delivery system

Abstract: BackgroundIron oxide nanoparticles are of considerable interest because of their use in magnetic recording tape, ferrofluid, magnetic resonance imaging, drug delivery, and treatment of cancer. The specific morphology of nanoparticles confers an ability to load, carry, and release different types of drugs.Methods and resultsWe synthesized superparamagnetic nanoparticles containing pure iron oxide with a cubic inverse spinal structure. Fourier transform infrared spectra confirmed that these Fe3O4 nanoparticles c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 45 publications
4
38
0
Order By: Relevance
“…In other words, the decrease in the intensity of the peak at 1121 cm −1 ( C S /ring vibration) in Fig. 2a and c also suggests the participation of an exocyclic (S) atom with chitosan to elucidate adsorption and/or encapsulation process of 6-MP with CNPs [28]. The results of the X-ray diffraction (XRD) analysis are depicted in Fig 3.…”
Section: Synthesis and Characterization Of 6-mp-cnpsmentioning
confidence: 88%
See 2 more Smart Citations
“…In other words, the decrease in the intensity of the peak at 1121 cm −1 ( C S /ring vibration) in Fig. 2a and c also suggests the participation of an exocyclic (S) atom with chitosan to elucidate adsorption and/or encapsulation process of 6-MP with CNPs [28]. The results of the X-ray diffraction (XRD) analysis are depicted in Fig 3.…”
Section: Synthesis and Characterization Of 6-mp-cnpsmentioning
confidence: 88%
“…Precisely, 200 L cell suspension was seeded in 96-well microplates (Corning ® , USA) at a density 25,000 cells/well and incubated for 24 h, after which the cells were exposed to a graded concentration of 6-MP and 6-MPCNPs, incubated in 5% CO 2 incubator at 37 • C for 24 h. The treated cells were incubated with 100 L of MTT reagent for 3 h. The culture medium was aspirated and 200 L of DMSO was added and cell viability was determined by measuring the absorbance on a microplate reader (SPECTROstarNano, BMG LABTECH, Germany) at 570 nm [27,28]. Untreated cells were used as controls.…”
Section: Determination Of Cytotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Various nanostructures of hydroxyapatite (Andronescu et al 2013;Venkatesan et al 2011;Wang et al 2009), magnetite (Daumann et al 2014;Dorniani et al 2013), zirconia (Batra et al 2013;Tang et al 2010), titania (Hou et al 2014;Aw et al 2012), silica (Bernal et al 2014;Xu et al 2013) etc., have already gained attention due to their efficacy in the fabrication of biosensors and nanocarriers for targeted delivery of drugs as well as substrates for immobilization of biomolecules. Among the various inorganic materials, titania (TiO 2 ) holds great promise in biomedical applications owing to its wide availability, biological as well as chemical inertness and have so far been reported in various morphological forms such as nanoparticles (Liang et al 2013), nanorods (Pang et al 2013), nanowires (Sun and Wu 2013), nanosheets , nanotubes (Pandikumar and Ramaraj 2013), mesopores (Mascolo 2013), and hollow spheres (Zhao and Middelberg 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports showed that a variety of active compounds such as kojic acid [19], doxorubicin [20,21], 5-aminosalicylic acid [22], 6-mercaptopurine [23], 10-hydroxycamptothecin [24], gallic acid [25,26], folic acid [27], arginine [28], and anthranilic acid [29] can be loaded onto the surface of magnetic nanoparticles.…”
Section: Introductionmentioning
confidence: 99%